2017
DOI: 10.15252/emmm.201607461
|View full text |Cite
|
Sign up to set email alerts
|

SPINK2 deficiency causes infertility by inducing sperm defects in heterozygotes and azoospermia in homozygotes

Abstract: Azoospermia, characterized by the absence of spermatozoa in the ejaculate, is a common cause of male infertility with a poorly characterized etiology. Exome sequencing analysis of two azoospermic brothers allowed the identification of a homozygous splice mutation in SPINK2, encoding a serine protease inhibitor believed to target acrosin, the main sperm acrosomal protease. In accord with these findings, we observed that homozygous Spink2 KO male mice had azoospermia. Moreover, despite normal fertility, heteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 46 publications
2
61
0
6
Order By: Relevance
“…We found the turkey acrosin‐like specific peptide (SLQEYVEPYRVLQEAKVQLIDL) in the chicken acrosin sequence. Recently by coexpression of acrosin and SPINK2 proteins in human cell line HEK293, it was demonstrated that SPINK2 prevents cell proliferation arrest induced by proacrosin (Kherraf et al, ). We thus conclude that, in the chicken, like in the mouse, SPINK2 regulates the activity of acrosin to prevent uncontrolled/deleterious sperm proteolysis and too early acrosome reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found the turkey acrosin‐like specific peptide (SLQEYVEPYRVLQEAKVQLIDL) in the chicken acrosin sequence. Recently by coexpression of acrosin and SPINK2 proteins in human cell line HEK293, it was demonstrated that SPINK2 prevents cell proliferation arrest induced by proacrosin (Kherraf et al, ). We thus conclude that, in the chicken, like in the mouse, SPINK2 regulates the activity of acrosin to prevent uncontrolled/deleterious sperm proteolysis and too early acrosome reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse, Spink2 genomic invalidation demonstrated the importance of the protein at the gonadic level. SPINK2 allowed spermatid differentiation and acrosome formation during spermatogenesis and was still present on the acrosome of mature sperm of mouse and human to protect it from proteolysis (Kherraf et al, ). In the present study, we demonstrated a role of SPINK2 at the postgonadic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mgat1 gene encodes the enzyme N‐acetylglucosaminyltransferase that regulates ERK signaling (Biswas, Batista, Sundaram, & Stanley, ), which is indispensable for spermatogenesis and Mgat1 deletion in spermatogonia did not produce any sperm (Batista, Lu, Williams, & Stanley, ). Likewise, spink2 deficient mouse have increased serine protease activity, disrupted spermatogenesis, and germ cell apoptosis (B. Lee et al, ), while the spink2 knockout homozygous male mice are azoospermic (Kherraf et al, ). The Slc16a7 (monocarboxylate transporter‐2) that transports lactate from Sertoli to germ cells was previously reported predominantly in spermatocytes and spermatids (Yadav et al, ) and genetic variations in MCT‐2 have clinical relevance in male infertility (J. Lee, Lee, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only Spink2 is expressed in testes. Thus, it is considered essential for spermatogenesis [16, 17]. Moreover, Spink2 is necessary to inactivate acrosin during its transit through the endoplasmic reticulum and the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%